O final do ciclo gráfico paleolítico do Vale do Côa: A arte móvel do Fariseu (Muxagata, Vila Nova Foz Côa) - Santos, André Tomás; Aubry, Thierry; Barbosa, António Fernando; García-Díez, Marcos; Sampaio, Jorge Davide (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
We present in this work the integral study of the portable art of Fariseu (Côa Valley). Eighty-five engraved pieces and four painted ones form the studied collection. The chronological attribution to the Late Dryas/ beginning of the Pre-boreal is perfectly assured by the stratigraphic origin of the pieces. The technical and stylistic attributes of the figures are similar to some of the rock art of the Côa valley, making the collection an important chronological referent to a vast number of engraved and painted panels of the region. Those technical and stylistic attributes are also similar to others from Southwest Europe that are dated from the end of the Late glacial period, which denotes the affiliation of this rock art facies in a graphic tradition of a broader geographic range.